Oxford handbook on the sources of international law - Knuchel, Sévrine; Besson, Samantha, 1973-; D'Aspremont, Jean (Oxford : Oxford University Press, 2017)
The question of the sources of international law inevitably raises some well-known scholarly controversies: where do the rules of international law come from? And more precisely: through which processes are they made, how are they ascertained, and where does the international legal order begin and end? These traditional questions bear on at least two different levels of understanding. First, how are international norms validated as rules of international. The Oxford Handbook of the Sources of International Law is the very first comprehensive work of its kind devoted to the question of the sources of international law. It provides an accessible and systematic overview of the key issues and debates around the sources of international law. It also offers an authoritative theoretical guide for anyone studying or working within but also outside international law wishing to understand one of its most foundational questions. Thisandbook features original essays by leading international law scholars and theorists from a range of traditions, nationalities and perspectives, reflecting the richness and diversity of scholarship in this area. --
Part I. The histories of the sources of international law -- Part II. The theories of the sources of international law -- Part III. The functions of the sources of international law -- Part IV. The regimes of the sources of international law.
Includes bibliographical references and index.
Keywords: International law -- Sources; International law -- Sources; Law; Sources